Prayer or Prison: The Unconstitutionality of Mandatory Faith-Based Substance Abuse Treatment - Meissner, Christopher M. (2006)
Whether faith-based substance abuse treatments are effective is certainly a valid question in its rightful place, but it is not the inquiry pursued here. Rather, this Note argues that a drug court's act of assigning unwilling offenders to twelve-step or otherwise religiously-based residential treatment centers violates the Establishment Clause guarantee. Specifically, such centers regulate the offenders' beliefs and compel them to affirm whatever tenets are professed at the individual treatment center. Moreover, a court's subsequent act of threatening or actually imposing criminal sanctions upon offenders for refusing to complete such treatment programs constitutes punishment for refusing to be religiously indoctrinated by a program mandated by the state. Regulations currently imposed upon federally funded faithbased treatment centers adequately safeguard offenders' First Amendment rights in these respects, but those regulations must be made applicable to all treatment centers that accept offenders from any court across the country